2012
DOI: 10.1890/es12-00217.1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and drivers of ectomycorrhizal fungal communities across the North American Arctic

Abstract: Abstract. Ectomycorrhizal fungi (EMF) form symbioses with a few plant species that comprise a large fraction of the arctic vegetation. Despite their importance, the identity, abundance and distribution of EMF in the Arctic, as well as the key drivers controlling their community composition are poorly understood. In this study, we investigated the diversity and structure of EMF communities across a bioclimatic gradient spanning much of the North American Arctic. We collected roots from two principal arctic ecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
85
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 81 publications
9
85
3
3
Order By: Relevance
“…Previous studies on belowground diversity of arctic ECM fungi that used similar methods, reported between 73 and 202 OTUs of ca. 12 genera (Bjorbækmo et al ., 2010; Geml et al ., 2012; Timling x0026; Taylor, 2012; Timling et al ., 2012, 2014). Moreover, several genera remain undersampled in our dataset (e.g., Lactarius , Amanita ), possibly due to their small genet size and relative rarity at the landscape scale.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies on belowground diversity of arctic ECM fungi that used similar methods, reported between 73 and 202 OTUs of ca. 12 genera (Bjorbækmo et al ., 2010; Geml et al ., 2012; Timling x0026; Taylor, 2012; Timling et al ., 2012, 2014). Moreover, several genera remain undersampled in our dataset (e.g., Lactarius , Amanita ), possibly due to their small genet size and relative rarity at the landscape scale.…”
Section: Discussionmentioning
confidence: 99%
“…Ectomycorrhizal (ECM) fungi are the predominant fungal guild in the Arctic (Gardes x0026; Dahlberg, 1996; Clemmensen et al ., 2006; Bjorbækmo et al ., 2010). Recent studies of belowground Arctic ECM fungal communities, revealed higher species richness than what had previously been known from aboveground surveys (Ryberg et al ., 2009; Bjorbækmo et al ., 2010; Geml et al ., 2012; Timling et al ., 2012; Timling x0026; Taylor, 2012). These studies indicated that the most diverse arctic ECM genera are Tomentella (here interpreted as including Thelephora) , Inocybe , Cortinarius , Sebacina , Russula, and Hebeloma .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…EMF species richness is very high, including generalist fungi with low host specificity and specialists associating only with certain host tree genera. Arctic EMF have been suggested to possess low specificity in terms of host choice (Ryberg et al, 2009;Timling et al, 2012). Therefore, tree populations will most likely find compatible EMF symbionts, especially since EMF show very long-distance dispersal (Geml et al, 2012).…”
Section: Biomass Allocation Between Host Tree and Ectomycorrhizal Fungimentioning
confidence: 99%